Reflective and Non-conscious Responses to Exercise Images - Cope, Kathryn; Vandelanotte, Corneel; Short, Camille E.; Conroy, David E.; Rhodes, Ryan E.; Jackson, Ben; Dimmock, James A.; Rebar, Amanda L. (Frontiers in Psychology, 2018)
Images portraying exercise are commonly used to promote exercise behavior and to measure automatic associations of exercise (e.g., via implicit association tests). The effectiveness of these promotion efforts and the validity of measurement techniques partially rely on the untested assumption that the images being used are perceived by the general public as portrayals of exercise that is pleasant and motivating. The aim of this study was to investigate how content of images impacted people’s automatic and reflective evaluations of exercise images. Participants (N = 90) completed a response time categorization task (similar to the implicit association test) to capture how automatically people perceived each image as relevant to Exercise or Not exercise. Participants also self-reported their evaluations of the images using visual analogue scales with the anchors: Exercise/Not exercise, Does not motivate me to exercise/Motivates me to exercise, Pleasant/Unpleasant, and Energizing/Deactivating. People tended to more strongly automatically associate images with exercise if the images were of an outdoor setting, presented sport (as opposed to active labor or gym-based) activities, and included young (as opposed to middle-aged) adults. People tended to reflectively find images of young adults more motivating and relevant to exercise than images of older adults. The content of exercise images is an often overlooked source of systematic variability that may impact measurement validity and intervention effectiveness.